2015
DOI: 10.1515/intag-2015-0005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reclamation on the structure of silty-clay soils irrigated with saline-sodic waters

Abstract: The objective of the work was to evaluate, by using the micromorphometric method, the effects of reclamation on porosity of two different clay loam soils irrigated with saline-sodic waters. Soil samples of the Ap horizon were put in cylindrical containers and irrigated with 9 types of saline-sodic waters (3 levels of salinity combined with 3 levels of sodicity). After a 4-year period, correction treatments were initiated by addition of calcium sulphate and leaching until electrical conductivity and sodium abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…can cause soil losses and runoff (Cucci, Lacolla, Pagliai, & Vignozzi, 2015;Huang, Zhang, Hu, & Zhao, 2015;Jordán, Zavala, Nava, & Alanís, 2009;Safari, Kavian, Parsakhoo, Saleh, & Jordán, 2016). In the experimental substrates, an important reduction of the bulk density was only found in those amended with compost and especially with woodchip mulch, compared with the high density value of the control substrates (without any treatment).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…can cause soil losses and runoff (Cucci, Lacolla, Pagliai, & Vignozzi, 2015;Huang, Zhang, Hu, & Zhao, 2015;Jordán, Zavala, Nava, & Alanís, 2009;Safari, Kavian, Parsakhoo, Saleh, & Jordán, 2016). In the experimental substrates, an important reduction of the bulk density was only found in those amended with compost and especially with woodchip mulch, compared with the high density value of the control substrates (without any treatment).…”
Section: Discussionmentioning
confidence: 89%
“…In restored plots, the combination of woodchip and sewage sludge induced a higher percentage of fissures (83.3%) than did the control. Many authors have similarly reported that low porosity and high bulk density can cause soil losses and runoff (Cucci, Lacolla, Pagliai, & Vignozzi, ; Huang, Zhang, Hu, & Zhao, ; Jordán, Zavala, Nava, & Alanís, ; Safari, Kavian, Parsakhoo, Saleh, & Jordán, ). In the experimental substrates, an important reduction of the bulk density was only found in those amended with compost and especially with woodchip mulch, compared with the high density value of the control substrates (without any treatment).…”
Section: Discussionmentioning
confidence: 99%
“…The correction of soil salinity by leaching is even more complicated if the clay fraction is dominated by minerals such as swelling montmorillonite. After water application, due to salt leaching the clay particles swell quickly, reduce the hydraulic conductivity and the macropores that are the main drainage ways (Quadir et al 2008;Cucci et al 2015).…”
mentioning
confidence: 99%
“…The use of saline water for irrigation purposes is increasingly popular in some countries and regions including India, China, Italy, and the USA [61][62][63][64]. Particularly, drip irrigation with saline water was widely applied to reclaim saline soil for planting cotton in the semiarid and arid saline-alkali region of China [65,66], and for constructing ecological landscapes in coastal regions [67,68].…”
Section: Scenarios Settingmentioning
confidence: 99%